Facilitating exercise adherence among Kuala Selangor, Malaysia antenatal women: a study protocol - Md Yunus, Nur Farhana; Abdul Manaf, Rosliza; Kadir, Hayati; Ismail, Suriani; Alagirisamy, Parwathi (International Journal of Public Health Science (IJPHS), 2024)
Antenatal exercise is recommended for antenatal women for its numerous benefits. Despite knowing the advantages of exercise, most antenatal women are less active during pregnancy. It is vital to address women's knowledge, attitudes, and barriers facilitated by a behavioural theory while developing an intervention. This study’s objective is to assess the effectiveness of antenatal exercise intervention based on behavioural theory in facilitating exercise adherence among antenatal women in Kuala Selangor, Malaysia. This study enrolled 220 pregnant women from six primary health clinics in the sub-urban district in a two-arm, cluster randomised controlled trial. Data will be collected in three phases: before the intervention, immediately and one-month post-intervention. The primary outcome measure is antenatal women's adherence to exercise, which will be assessed via a self-reported Exercise Adherence Rating Scale questionnaire. The intervention in this protocol is designed based on the information, motivation and behavioral (IMB) model to facilitate antenatal women's adherence to antenatal exercise, promoting an active lifestyle and reducing maternal complications. The findings may contribute to developing a future intervention that will promote more active lifestyles during pregnancy, which would increase overall health-related quality of life.